2005
DOI: 10.1074/jbc.m500002200
|View full text |Cite
|
Sign up to set email alerts
|

A Double Mutation in the Extracellular Ca2+-sensing Receptor's Venus Flytrap Domain That Selectively Disables l-Amino Acid Sensing

Abstract: The extracellular Ca 2؉ -sensing receptor is activated allosterically by L-amino acids, and recent molecular analysis indicates that amino acids are likely to bind in the receptor's Venus flytrap domain. In the current study we set out to identify residues in the VFT domain that specifically support amino acid binding and/or amino acid-dependent receptor activation. Herein we describe two mutations of the Ca 2؉ -sensing receptor (CaR) Venus Flytrap domain, T145A and S170T, that specifically impair amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 22 publications
(15 reference statements)
2
59
0
Order By: Relevance
“…5C) whereas HEK-293 cells expressing the T145A/S170T double mutant CaR exhibited no change in Ca 2ϩ o sensitivity (Fig. 5D) as reported previously (15).…”
Section: Effects Of ␥-Glutamyl Peptides On Casupporting
confidence: 86%
See 3 more Smart Citations
“…5C) whereas HEK-293 cells expressing the T145A/S170T double mutant CaR exhibited no change in Ca 2ϩ o sensitivity (Fig. 5D) as reported previously (15).…”
Section: Effects Of ␥-Glutamyl Peptides On Casupporting
confidence: 86%
“…S1). The results indicate that ␥-glutamyl peptides and S-methylgluta- (14) and glutathione (21) binding sites to the VFT domain and we previously identified T145A/S170T as a double mutant form of the VFT domain with near-normal Ca 2ϩ o -sensitivity but markedly impaired L-amino acid sensing (15). In the current study, we first confirmed that this mutant exhibited normal or near-normal Ca 2ϩ o sensitivity in the absence of L-Phe or S-methylglutathione (Fig.…”
Section: Effects Of ␥-Glutamyl Peptides On Camentioning
confidence: 66%
See 2 more Smart Citations
“…All mutants were generated in pcDNA3.1(+)-WTCaSR and/ or pcDNA3.1(+)-WTCaSR(FLAG) plasmid, which contains the FLAG epitope DYKDDDDK between residues 371 and 372; insertion of the FLAG epitope at this position has been shown previously to have no impact on receptor function [21]. The Quikchange II sitedirected mutagenesis protocol was used to introduce the point mutations F706A, L797A and E803A.…”
Section: Construction Of Mutant Receptorsmentioning
confidence: 99%